HMGB1 Recruits TET2/AID/TDG to Induce DNA Demethylation in STAT3 Promoter in CD4+ T Cells from aGVHD Patients - Xuejun Xu; Yan Chen; Enyi Liu; Bin Fu; Juan Hua; Xu Chen; Yajing Xu (Journal of Immunology Research)
STAT3 is highly expressed in aGVHD CD4+ T cells and plays a critical role in inducing or worsening aGVHD. In our preceding studies, DNA hypomethylation in STAT3 promoter was shown to cause high expression of STAT3 in aGVHD CD4+ T cells, and the process could be modulated by HMGB1, but the underlying mechanism remains unclear. TET2, AID, and TDG are indispensable in DNA demethylation; meanwhile, TET2 and AID also serve extremely important roles in immune response. So, we speculated these enzymes involved in the STAT3 promoter hypomethylation induced by HMGB1 in aGVHD CD4+ T cells. In this study, we found that the binding levels of TET2/AID/TDG to STAT3 promoter were remarkably increased in CD4+T cells from aGVHD patients and were significantly negatively correlated with the STAT3 promoter methylation level. Simultaneously, we revealed that HMGB1 could recruit TET2, AID, and TDG to form a complex in the STAT3 promoter region. Interference with the expression of TET2/AID/TDG inhibited the overexpression of STAT3 caused by HMGB1 downregulation of the STAT3 promoter DNA methylation. These data demonstrated a new molecular mechanism of how HMGB1 promoted the expression of STAT3 in CD4+ T cells from aGVHD patients.